2003
DOI: 10.1103/physrevlett.90.114301
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Self-Assembly and Patterns in Electrostatically Driven Granular Media

Abstract: We show that granular media consisting of metallic microparticles immersed in a poorly conducting liquid in strong DC electric field self-assemble a rich variety of novel phases. These phases include static precipitate: honeycombs and Wigner crystals; and novel dynamic condensate: toroidal vortices and pulsating rings. The observed structures are explained by the interplay between charged granular gas and electrohydrodynamic convective flows in the liquid.PACS numbers: 45.70.Qj,05.65.+b,47.15.Cb,47.55.Kf Un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 14 publications
6
76
0
Order By: Relevance
“…In the present case, clay is more conducting than the surrounding liquid, and we therefore exclude Quincke rotation as the mechanism here. However, our observations are in line with previous work showing that conducting particles in bulk can assemble and form counter-rotating vortices38.…”
Section: Resultssupporting
confidence: 93%
“…In the present case, clay is more conducting than the surrounding liquid, and we therefore exclude Quincke rotation as the mechanism here. However, our observations are in line with previous work showing that conducting particles in bulk can assemble and form counter-rotating vortices38.…”
Section: Resultssupporting
confidence: 93%
“…For example, dipolar particles subjected to a magnetic or electric eld have been shown to form patterns. [30][31][32] Self-assembly and clustering behavior in active matter have been analyzed from the swim stress perspective, 2 and it would be straightforward to extend these ideas to self-propelled particles that are biased by an external orienting eld.…”
Section: Discussionmentioning
confidence: 99%
“…As a physical phenomenon to study, many researchers have interest in the behavior of small particles (Ͻ Ͻ1mm) in a known electric field, where particles used are conductive and the electric field is obtained from a pair of plates with a/d voltage. They found that granular cluster pattern differs with the voltage set [12][13][14] and is affected by humidity. 15 A similar phenomenon was observed 2 for larger particles (2.8mm) where three characteristic aggregation patterns (clusters, half-ring, and ring) were formed in a vertical pipe due to electrostatic effects in a pneumatic conveying system.…”
Section: Introductionmentioning
confidence: 97%